Sixth Street Residence - Michael Rotondi; Tom Mayne (Oz, 1987)
Program: The reconstruction of an existing duplex to the specifications required of the new owner. Site: 60' x 60' parcel @ the corner of a typical residential street and an alley in Santa Monica, Calif.